Relationships Between Protein Content and Chemical Compositions of Local Dry Bean (Phaseolus vulgaris L.) Genotypes Grown in Turkey - Harmankaya, Mustafa; Karadas, Serdar; Palta, Cetin; Ceyhan, Ercan (Asian Journal of Chemistry, 2010)
In present study, bean local genotypes grown in the Central Anatolian Province of Turkey have been analyzed to determine and compare their protein and mineral contents. Statistically significant variations were found amongst the genotypes for all variables. The protein and minerals analyzed for all bean genotypes show that protein varies 18.33 to 23.67 %, potassium from 963.3 to 1140 mg/100 g, phosphorus from 310.9 to 423.9 mg/100 g, calcium from 125.1 to 322.0 mg/100 g, magnesium from 90.25 to 105.9 mg/100 g, sulfur from 136.6 to 181.3 mg/100 g, sodium from 25.47 to 45.17 mg/100 g, manganese from 1.70 to 3.27 mg/100 g, iron from 3.84 to 8.41 mg/100 g and zinc from 2.09 to 2.85 mg/100 g. Positive and significant relationships were found statistically between protein and potassium, protein and phosphorus, protein and magnesium, protein and sulfur and protein and iron. The results show that bean genotypes can serve as a significant source of protein and minerals to meet the demand of populations living in Turkey.